Reuse of residues generated by civil construction: a brief review (Research, Society and Development, 2019)
Reuse of waste generated by the construction has been seen as an important practice for the environment, the use of the RCC has become every day more, on account of its techniques and its results. Recycling and reusing the rubble of construction if you can promote a culture where all begin an environmental responsibility, making the works become reference to sustainability in the construction area. Besides being slightly compromised with the importance of the impacts to the environment, companies that undertake to join the RCC your profitability and decrease the impacts that will be caused to the environment. This article comes to address the types of materials that can be reused, which your classification in accordance with resolution 307/02 of CONAMA, the techniques that are needed to make the reuse of residue, what are the advantages of doing the reuse, and which impacts of this waste recycling can generate.